Evaluation of the effectiveness of the presentation of virtual histology slides by students during classes. Are there any differences in approach between dentistry and general medicine students? - Tauber, Zdenek; Cizkova, Katerina; Lichnovska, Radka; Lacey, Helena; Erdosova, Bela; Zizka, Radovan; Kamarad, Vojtech (European journal of dental education, 2019)
INTRODUCTION: Virtual microscopy, used as a method to teach histology, has many undeniable advantages. However, the usefulness of this method is somewhat limited by the difficulties students face in finding their way through huge amounts of digital data, compounded by decreased interaction between students and teachers. We describe the results of a recent pilot project which combined the modern teaching methods of active learning, where students themselves present histological slides and make use of the virtual microscopy system. METHODS: Students' responses to a structured questionnaire and examination results were evaluated. RESULTS: We found that a combination of both electronic materials and textbooks was commonly used by students to prepare for practical teaching sessions, with electronic resources being used regularly by the majority of students. No statistically relevant differences were found between the approaches of dentistry vs general medicine students. Cooperation between students' groups during the preparation for individual presentations was seen to be beneficial by a majority of dentistry students; they reported that the introduction of student-led presentations improved their quality of preparation for practical lessons, as well as increasing their participation and activity level in the lessons themselves. These different approaches and motivations between students of dentistry and general medicine are reflected in the test results where dentistry students are more successful. CONCLUSION: We confirm that there are differences in motivation, approaches and examination results between both groups of students, which should be taken into account and which could lead to differentiation of future curricula for both study courses.
Keywords: Histology; Surveys and Questionnaires; Humans; mikroskopie; studenti lékařství; učení; Female; lidé; Virtual Reality; učební pomůcky; pilotní projekty; studium stomatologie; průzkumy a dotazníky; Pilot Projects; Teaching Materials; ženské pohlaví; studenti stomatologie; Male; Learning; Education, Dental; virtuální realita; vyučování; Students, Medical; Teaching; Microscopy; mužské pohlaví; histologie; Students, Dental